Teleology and Educational Theory in Greenland: Contributing to a Theory of Change for The Good School - Søndergaard, Per (Études Inuit Studies, 2023)
This article aims to explore what can be done to ensure that fewer children and young people in Greenland opt out of education. In doing so, I hope to contribute to the debate on a theory of change for the Atuarfitsialak educational reform, also known as “The Good School.” The assumption behind the article is that prominent Greenlandic intellectuals are correct in their assessment that the main reason why children and young people drop out of secondary school is that the school—as a system—is still too Danish and does not reflect the Inuit traditional form of knowledge. Furthermore, the article asserts that there is a connection between the Inuit worldview and teleology in the Aristotelian sense, and that the problem with the school system is to be understood as a conflict between the dominant scientistic form of knowledge and other forms of knowledge. The article then discusses the basis for a theory of educational didactics that pursues a non-hierarchical approach to diverse forms of knowledge, including teleology.